Micro Entrepreneur Capacity Building through Financial Management and Marketing Strategy Training for MSME Actors - Hasyim, Hasyim; Bakri, Muhammad (Celebes Journal of Community Services, 2025)
This study explores the integration of financial management and marketing strategies in capacity-building programs to enhance the performance of micro, small, and medium enterprises (MSMEs). It aims to address gaps in existing research by proposing a holistic framework that synergizes these two critical elements to foster sustainable growth and competitiveness. Employing a systematic literature review (SLR) methodology, this research consolidates findings from peer-reviewed studies published between 2018 and 2024. The review focuses on identifying best practices, challenges, and actionable insights relevant to MSME capacity building, with an emphasis on integrating financial and marketing capabilities. The findings reveal that financial literacy and digital marketing strategies are crucial for MSME growth. Financial literacy empowers MSME actors to manage resources, mitigate risks, and adopt advanced financial technologies. Concurrently, digital marketing enhances market reach, customer engagement, and brand loyalty. The study highlights the strong synergy between these elements, where effective financial management supports innovative marketing strategies, and successful marketing generates revenue streams that reinforce financial stability. This integrated approach enhances operational efficiency, resilience, and scalability, especially in volatile market conditions exacerbated by the COVID-19 pandemic. This study provides significant contributions to both academic literature and practical applications. It highlights the need for policymakers to design sector-specific, integrated training programs and encourages MSME actors to adopt holistic strategies for capacity building. Future research should focus on validating the proposed framework through primary data and exploring additional dimensions, such as technological innovation and workforce development.